Clinical aspects of newborns admitted to a neonatal intensive care unit (International Seven Journal of Health Research, 2024)
Objective: To identify the clinical profile of newborns admitted to Neonatal Intensive Care Units. Methodology: This is an ecological observational study, with a quantitative approach, using data from newborns admitted to Neonatal Intensive Care Units in hospitals in the municipality of Cascavel in the western region of Paraná, Brazil. The following variables were studied: gender, color/race, type of delivery, gestational age, number of prenatal consultations, mother's age, mother's level of education, birth weight, congenital malformation, type of congenital malformation, Apgar score. Results: Based on the results of this study we can identify that the newborns, the majority were male, born by caesarean section, most of them considered adequate for gestational age (AIG), being less than 2,500grams, with apgar scores in the 1st and 5th minutes considered between normal and moderate. Discussion: Knowing the main hospitalization diagnoses and the main reasons for premature births, it is suggested that relationship studies be carried out to compare the variables studied, enhancing understanding of the findings, as well as studies of interventions carried out after identifying results similar to those of this study, in order to identify whether knowing the profile of those admitted to the Neonatal ICU, it is possible to intervene to prevent and avoid damage and sequelae. Conclusion: However, this research has provided insight into the population studied in terms of their growth and the practices carried out in the unit, bringing contributions to the service, enabling changes in the management of these babies and all those who contribute to their development.